Making women's history : (The Feminist Press at the City Univ., 2000)
Mary Ritter Beard can be considered the “founding mother” of the field of American women’s history. A visionary thinker, Beard devoted her life to reconstructing a history that had remained largely undocumented and unacknowledged before she began her ground-breaking work. She held a firm conviction that women had a far greater impact on history than male historians had ever recognized, and that a knowledge of their own history would enable women to realize their full potential as active members of society and agents of social change.